Implementation of E-Government in the Bill Payment Mechanism of the Vendor Invoicing Port (VIP) Application at PT PLN (Persero) Pusharlis UP2W1 Cilegon - Aulia, Ummi Khoirotul; Berthanila, Rethorika (Future Science, 2024)
Implementing e-government in the business sector of State-Owned Enterprises (BUMN) has become a strategic step to enhance operational efficiency and transparency. This study aims to analyse the Vendor Invoicing Portal (VIP) application implementation at PT PLN (Persero) PUSHARLIS UP2W I Cilegon based on three main elements: support, capacity, and benefits. (value). Data were collected through in-depth interviews, direct observation, and document analysis using a descriptive qualitative method. The research results indicate that regulatory support through Presidential Regulation No. 95 of 2018 has provided a strong legal foundation. Still, the dissemination of the application to new vendors has not been optimal. From the aspect of capacity, the technological infrastructure is mostly adequate, but the limitation of human resources with information technology competence poses a significant challenge. In terms of benefits, the VIP application successfully increased payment efficiency by 50%, reduced administrative errors by 80%, and improved vendor satisfaction by 75%. This study concludes that the synergy between support, capacity, and system benefits greatly influences the success of e-government implementation at PT PLN PUSHARLIS. Recommendations include enhancing HR training programs, intensive vendor outreach, and investing in digital infrastructure to support sustainable digital transformation